2013
DOI: 10.1002/ajmg.a.35966
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of hepatic adenomas in patients with wolf‐hirschhorn syndrome: A new rare complication?

Abstract: Wolf-Hirschhorn syndrome (WHS) is a rare microdeletion syndrome associated with a characteristic facial appearance, failure to thrive, psychomotor delays, and various major malformations of internal organs; many medical complications have been described (feeding difficulties, epilepsy, hearing problems). Benign or malignant oncologic problems are not a typical feature of the natural history of these patients. We report on two patients with WHS patients in whom hepatic adenoma (HA) were diagnosed during adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
1
18
0
2
Order By: Relevance
“…This is caused by the muscular hypotonia, gastroesphegal reflux and recurrent aspiration [8]. Hypotonia may also result in swallowing difficulties and other gastrointestinal disorders (including hepatic adenomas) [19].…”
Section: Congenital Defectsmentioning
confidence: 99%
“…This is caused by the muscular hypotonia, gastroesphegal reflux and recurrent aspiration [8]. Hypotonia may also result in swallowing difficulties and other gastrointestinal disorders (including hepatic adenomas) [19].…”
Section: Congenital Defectsmentioning
confidence: 99%
“…The only possible causal relationship between WHS and the hepatic adenoma was due to the hyperandrogenemia side‐effect of the anti‐epileptics. The authors indicated that chromosomal anomalies involving the distal portion of chromosome 4 have been identified as being associated with various malignancies other than hepatic tumors . WHSCR exists at the most distal part of the short arm of chromosome 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually have seizures until 3 years of age, and majority of them have mental or motor retardation . Cancer is not a frequent feature of the syndrome, but hematopoietic system malignancies and hepatic adenoma have been reported in a few cases . Herein, we report a pediatric patient with WHS who developed hepatoblastoma.…”
mentioning
confidence: 96%
“…До таких захворювань належить синдром Вольфа -Хіршхорна, при яко-му життєдіяльність обмежена у зв'язку з наявними грубими фізичними вадами розвитку та глибокою розумовою відсталістю [3,8].…”
Section: нас не бачать… нас не чують… про нас не говорять… думають нunclassified
“…До таких захворювань належить синдром Вольфа -Хіршхорна, при яко-му життєдіяльність обмежена у зв'язку з наявними грубими фізичними вадами розвитку та глибокою розумовою відсталістю [3,8].На жаль, в Україні бракує розвинутих соціаль-них програм для підтримки дітей та їх родин із різ-ними орфанними захворюваннями. Батьки нерід-ко самостійно групуються із сім'ями, яких спіткало схоже горе.…”
unclassified